Retroperitoneal Ganglioneuroma in Childhood-A Presentation of Two Cases - Vahudin Zugor; Günter E. Schott; Reinhard Kühn; Apostolos P. Labanaris (Elsevier, 2009)
Ganglioneuromas are considered to be part of the neuroblastoma series of tumors, which evolve from the sympathogonia of neural crest origin. As imaging techniques have become more widely practiced, the number of ganglioneuromas detected incidentally has increased. Preoperative diagnosis of retroperitoneal ganglioneuromas is often difficult and the diagnosis is usually based on histopathological findings after surgical excision of the tumor. We present two cases of this unique disease entity and discuss its clinical presentation, therapeutic approach, and clinical outcome.